A Fuzzy Ga Based STATCOM for Power Quality Improvement - S. Deepa; S. Praba; V. Deepalakshmi; L. Jayaprakash; M. Manimurugan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
This paper deals with various power issues such as voltage sag, swell, harmonics, and surges using static synchronous compensator (STATCOM).The conventional controller suffers from uncertain parameters and non-linear qualities. However they are computationally inefficient extending to optimize the fuzzy controller (FC) parameters, since they exhaustively search the optimal values to optimize the objective functions. To overcome this drawback, a genetic algorithm (GA) based Fuzzy controller parameter optimization is presented in this paper. The GA algorithm is used to find the optimal fuzzy parameters for minimizing the objective functions. The feasibility of the proposed GA technique for distribution systems to improve the sag and total harmonic distortion (THD) as major power quality indices in sensitive loads at fault conditions has been simulated and tested. Therefore, the multi-objective optimization algorithm is considered in order to attain a better performance in solving the related problems.